Automotive Handling and Technology - Applegate , Arjun, author 645127 (Delhi, India : Orange Apple, 2012)
Automobile handling and vehicle handling are descriptions of the way wheeled vehicles perform transverse to their direction of motion, particularly during cornering and swerving. It also includes their stability when moving at rest. Handling and braking are the major components of a vehicle's "active" safety. The maximum lateral acceleration is sometimes discussed separately as "road holding". Automobiles driven on public roads whose engineering requirements emphasize handling over comfort and passenger space are named sports cars.